Developing creativity through ICT and Music Teachers’ Training: a biographical experience - Sadio-Ramos, Fernando José (2021)
The text is part of a qualitative biographical-narrative investigation in process, which proceeds by obtaining testimonies from teachers and researchers who train teachers with the help of ICT to promote the skills of creativity, collaboration, cooperation, and communication, understood as essential for the development of comprehensive education, promoting curricular sustainability and participatory citizenship. In this article, we report on the experience of a teacher and researcher, Cristina Arriaga Sanz, who dedicates her labor to teacher training in the field of Musical education in Spanish Higher Education, of which we will emphasize the close relationship of its contents with the theoretical contributions we present and with previous results obtained through our investigation.